Synchronization NIK to NPWP, Challenges to the Tax Payment System - Khasanah, Uswatun; Nuryati, Tutty; Yozi, Vitra (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The research was conducted with a sample of MSME (Small and Medium Enterprises) business actors who carry out culinary business activities. The research conducted observations with the aim of finding out how much respondents responded to the modernization of the tax administration system with the synchronization of NIK and NPWP. The research uses qualitative methods with research stages so that it produces output that can be accounted for. The questionnaire that could be processed was 81 respondents. Research states that respondents gave a choice on a scale of 5 for modernizing the tax administration system at 66.67% and synchronization NIK with NPWP at 33.33%. The public is aware of the new regulations from the DJP, but socialization needs to be carried out consistently with various media so that the public understands that every new regulation made is aimed at the welfare of the community.